IMPACT OF FAMILY ECONOMIC BACKGROUND ON THE EDUCATIONAL ACHIEVEMENT OF SCHEDULED TRIBE STUDENTS IN CHHINDWARA DISTRICT: A SOCIO-ECONOMIC ANALYSIS - Jawre, Priti; Chaturvedi, Prakriti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research study analytically examines the educational achievements of Scheduled Tribe (ST) students residing in Chhindwara district of Madhya Pradesh in their socio-economic perspective. Using a quantitative methodology based on direct data from a total of 200 students, this research examines the interrelationship between factors such as family income, educational background of parents and access to educational resources and the academic performance of students. The study revealed that while about 55% of the students are scoring above average marks, the remaining 45% are below average due to economic poverty and lack of access to basic learning resources. Parental education plays a positive and motivating role in the educational progress of students, while limited digital access and unsuitable learning environment are proving to be a hindrance to their proper development. The study concludes by recommending targeted interventions such as financial assistance, availability of resources, and educational counseling for the educational advancement of Scheduled Tribe students.